An Historical Snapshot of the Relevance of Pregnancy for Lesbian Intimate Partner Violence - Macdonnell, Judith (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
Intimate partner violence (IPV) has been taken up with respect to heterosexual couplesfor several decades and strategies to address/support this have been integrated into health and social service programs and support. Pregnancy is one factor that has been associated with IPV. Nevertheless, despite the increasing attention to the lesbian babyboom from the mid-’70s in North America and affirmation of the diverse families who comprise communities and increasingly visible programming and services to meet the diverse needs of lesbians, less visible has been lesbian IPV and particularly in relation to motherhood, pregnancy or postpartum. This paper reports on an examination of scholarly literature on lesbian IPV and lesbian mothering undertaken in 2003 that suggested the limited visibility of childbearing in relation to lesbian IPV had implications for research and programming in a Canadian context. Ashistorical research, this inquiry aimed to be congruent with an advocacy stance, one that was accountable to lesbian communities The findings are situated in the current landscape of research and resources for childbearing lesbians given the uneven support for lesbian mothering and mothering-focused lesbian IPV.